Dialektika Status dan Peran Perempuan dalam Struktur Sosial Masyarakat Petani - Munandar Sulaeman; Siti Homzah (Jurnal Penelitian Kesejahteraan Sosial, 2013)
The aims of this study is to determine the status and role of women in family and social structure of dairy farmer; the role of women in the income earning and household (domestic ) work and; the dialectic process of status and role of women. The methods used on this research is case study with qualitative approach. Qualitative data analysis was done by categorizing and organizing data through in-depth understanding (verstehen understanding), both textual and contextual that were interpreted afterward. The result showed that the values of the status and role of women in family structure indicate a bargaining through a process of dialogue between husband and wife based on the potential and contribution in both the work of raising livestock and household; in social structure, the role of women as breadwinners have been accepted as a social reality through its participation in the dairy cattle business; working hours of women who poured out in the dairy cattle business and household activities for 8-10 hour per day, far greater than the man (6-10 hours per day); The process of dialectics in the aspect of culture, structure and the relational patterns indicate there has been a shift the values of culture where women have gained high appreciation in society of farmers and have been positioned strategically (as decision maker) in business of the family’s livehood and there are a functional partnership relations between men and women in dairy farmer community in the study area.